2022
DOI: 10.3389/fped.2022.966943
|View full text |Cite
|
Sign up to set email alerts
|

Solid pancreatic masses in children: A review of current evidence and clinical challenges

Abstract: Pancreatic tumors in children are infrequently encountered in clinical practice. Their non-specific clinical presentation and overlapping imaging characteristics often make an accurate preoperative diagnosis difficult. Tumors are categorized as epithelial or non-epithelial, with epithelial tumors further classified as tumors of the exocrine or endocrine pancreas. Although both are tumors of the exocrine pancreas, solid pseudopapillary neoplasm is the most prevalent solid pancreatic tumor in children, while pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 234 publications
1
21
0
4
Order By: Relevance
“…The median age of the patients in our study was 31 years, with pediatric patients accounting for 19% and young patients accounting for 58.1%, which is consistent with other reports [19][20][21] . Irtan S [22] reported that SPNs in the adult group were mainly located in the tail of the pancreas, and those in the pediatric group were mainly located in the head of the pancreas.…”
Section: Discussionsupporting
confidence: 92%
“…The median age of the patients in our study was 31 years, with pediatric patients accounting for 19% and young patients accounting for 58.1%, which is consistent with other reports [19][20][21] . Irtan S [22] reported that SPNs in the adult group were mainly located in the tail of the pancreas, and those in the pediatric group were mainly located in the head of the pancreas.…”
Section: Discussionsupporting
confidence: 92%
“…Patients with high-risk factors such as, large tumor size (>8cm), synchronous metastasis, lymphovascular invasion, pancreatic parenchymal invasion, and a high Ki-67 index (>4%), are related with recurrence. (10,(19)(20)(21)(22)(23) The WHO criteria for high grade transformation of SPN include "deep invasion into the surrounding tissue". (14,24) However, the definition of this criterion may be ambiguous.…”
Section: Resultsmentioning
confidence: 99%
“…16 children with SPN were treated during this period (88% girls). The median age of presentation was 12 years (IQR [9][10][11][12][13][14]. All children presented with abdominal pain.…”
Section: Methodsmentioning
confidence: 99%
“…In children, PDAC is associated with the worst prognosis of any pancreatic malignancy [3,7]. Amongst seven children and adolescents diagnosed with PDAC in the SEER 21 database, the fteen-year survival rate was 21% [2,4].…”
Section: Introductionmentioning
confidence: 99%